The Effectiveness of Employing Microteaching in Acquiring Teaching Skills for Students Teaching The Basic Stage in Al-Aqsa University- Gaza (Journal Of Educational and Psychological Researches, 2017)
The study aims to identify the effectiveness of employing microteaching in acquiring teaching skills of students teaching basic stage in Al-Aqsa University. The two researchers used the experimental method and a quota sample consisted of a group of (80) students who were distributed on the university two branches in Gaza and Khan younis and on males and females equally, and on four teaching courses counted (20) students for each. The study tool represented in an observation card ,and the results showed statistically significant differences between the level of all the skills of teaching and between the standard rate (75%) in favor of teaching skills, also showed statistically significant differences attributed to the variable of the university branch in favor of Khan younis branch, and statistically significant differences attributed to gender in favor of females, as well as statistically significant differences attributed to the variable of the type of course (Arabic language, mathematics, science, social studies) in favor of mathematics.